Perbedaan Dukungan Nenek dalam Keluarga Extended Family pada Pemberian ASI Eksklusif dan Tidak Eksklusif di Wilayah Kerja Puskesmas Arjasa Kabupaten Jember (The Differences of Grandmother Support in Extended Family on Exclusive and Non-Exclusive Breastfee - Dina Amalia; Ratna Sari Hardiani; Lantin Sulistyorini (Pustaka Kesehatan, 2018)
The rate of exclusive breastfeeding in Jember still low, it’s about 69.27% from the target is 80%.One factors of that is the lackness of family support, especially grandmother. Grandmother mantainto give early complementary foods to baby because of cultural reasons. The aim of this study was toanalyze the differences of grandmother support in extended family on exclusive and non-exclusivebreastfeeding in working area of Arjasa public health center. This research used an observationalanalytic design with Retrospective approach. The subjects was 66 mothers with babies aged 7-12months which divided in two groups, 22 of mothers who breastfeed exclusively dan 44 mothers whobreastfeed not exclusively that collected by multistage random sampling. Instrument usedquestionnaire. The analysis based on statistical Mann-Whitney showed p value = 0.001 (p value <α=0.05). It means there are the differences of grandmother support in extended family on exclusiveand non-exclusive breastfeeding. Grandmothers can affect the mothers to decided breastfeedexclusively. Informational support is the most important support to mothers. Health workers need toimprove mothers’s knowledge and involve grandmothers as effort giving exclusive breastfeeding, sothe rate of exclusive breastfeeding can be increased.Keywords: grandmother support, exclusive, non-exclusive, breastfeeding